The Study of Proteolytic Activity of Some Strains of Pectobacterium Carotovorum Representatives Phytopathogenic Bacteria - Marina Melkumyan; Bella Babayan; Marina Kinosyan; Tamara Davidyan; Gagik Mikaelyan (Interdisciplinary Science Studies, 2024)
Phytopathogenic microorganisms are one of the most harmful biotic factors negatively affecting on agriculture, horticulture and forestry. Proteases of various phytopathogens including bacteria and fungi are well-known, such as like the proteases of human and animal opportunistic pathogenic bacteria. And often a proteolytic activity is related to the pathogenicity and virulence of the mentioned microbes. One of the most common pathogens of plants is Pectobacterium carotovorum, which is also known as Bacillus carotovorum or Erwinia carotovora. Current research is devoted to the study of extracellular proteolytic activity of 24 strain P. Carotovorum.